2004
DOI: 10.1590/s0101-20612004000400016
|View full text |Cite
|
Sign up to set email alerts
|

Alterações bioquímicas post-mortem de matrinxã Brycon cephalus (Günther, 1869) procedente da piscicultura, mantido em gelo

Abstract: SUMMARY POST-MORTEM BIOCHEMICAL ALTERATIONS IN AQUACULTURED MATRINXÃ FISH Brycon cephalus (GÜNTHER, 1869) WHEN STORED ON ICE. Post-mortem biochemical alterations in aquacultured matrinxã fish Brycon cephalus (Günther, 1869) when stored on ice in Manaus-AM, were studied in this paper. The storage time on ice was determined through tasting and physical sensory evaluations, pH, total volatile bases nitrogen (TVB-N) and bacteriological analyses during 29 days. Rigor-mortis index, ATP-related compounds and K value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 6 publications
(6 reference statements)
4
9
1
8
Order By: Relevance
“…The results obtained in Treatment 1 are similar to those found by Albuquerque (), who found TVB‐N values for Nile tilapia, Oreochromis niloticus , below 21.40/100 g in the muscle of the fish slaughtered by stunning with CO 2 during day 17 of storage on ice. Batista et al (), however, evaluating the degradation of matrinxã, B cephalus , stunned in CO 2 and by asphyxia and stored on ice, found similar results on the 16th day of storage to those obtained on the 8th day of this study with Treatments 1 and 3.…”
Section: Resultssupporting
confidence: 84%
“…The results obtained in Treatment 1 are similar to those found by Albuquerque (), who found TVB‐N values for Nile tilapia, Oreochromis niloticus , below 21.40/100 g in the muscle of the fish slaughtered by stunning with CO 2 during day 17 of storage on ice. Batista et al (), however, evaluating the degradation of matrinxã, B cephalus , stunned in CO 2 and by asphyxia and stored on ice, found similar results on the 16th day of storage to those obtained on the 8th day of this study with Treatments 1 and 3.…”
Section: Resultssupporting
confidence: 84%
“…Pedrazzani et al (2009) also found similar results when comparing the effect of two desensibility methods for Nile tilapia, wherein the rigor mortis has been reached between 8 and 9 hours after slaughter. Moreover, Batista et al (2004) and Almeida et al (2005) mentioned that when slaughtering specimens of matrinxã (Brycon cephalus) and tambaqui (Colossoma macropomum) respectively, rigor mortis was established much earlier, between 30 and 75 minutes. This suggests that the species respond differently on this parameter, which may be related among other factors to the slaughter method and the muscle fiber profile of each species.…”
Section: Rigor Mortismentioning
confidence: 99%
“…Nevertheless, fish slaughtered immediately after transport showed pH above 6.5 at 28 days post-slaughter, whereas fish allowed to recover from transport stress obtained this level after 49 days of storage. Batista et al (2004) observed that farmed matrinxãs kept in ice initially exhibited lower pH values, increasing after 6 days. Almeida et al (2006) observed pH between 6.07 and 6.66 in farmed tambaquis kept in ice for 43 days, with a small variation in the first days of storage and a significant increase after 19 days.…”
Section: Discussionmentioning
confidence: 95%